The importance of women in livestock systems - Wright, Iain A. (International Livestock Research Institute, 2016)
Gender is an important dimension in livestock systems. Animals are a source of food and nutrients for people including for women and children, livestock provides an income, resources to send children to school, buy commodities, etc. Women are central to livestock rearing; they provide about 70% of the labour; they are critical to deciding how animal-sourced food is distributed during mealtimes. But women benefit only a little from their work: when it comes to selling the animals or their products, in most cases the men benefit. The question is how to ensure that all members of a household can benefit. When it comes to research there are two dimensions: strategic gender research which is about understanding the role played by men, women, children in the livestock systems, and who benefits or not. Second, is mainstreaming gender in other aspects of research. For example, in new technologies or health or breeding research, how do we ensure that new technologies benefit all. Strategic research is about understanding the social norms and dynamics which influence livestock systems. Limited research has been done on this: we are just starting to understand these dynamics. In the future, both strategic research and gender mainstreaming will be important. Scientists are open to thinking about gender, but often do not know how to deal with it. In the future we will do more to provide them with the tools to think through gender aspects. Interview with Iain Wright (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684